Preparation of viscoelastic gel‐like halloysite hybrids and their application in halloysite/polystyrene composites. Issue 10 (12th May 2017) - Yin, Xianze; Weng, Puxin; Yang, Shiwen; Han, Lu; Du, Zhengliang; Wang, Luoxin; Tan, Yeqiang
Abstract: Self‐reinforcement gel‐like halloysite nanotube ( g ‐HNT) hybrids with various viscoelastic behaviors were fabricated by firstly treating with various concentrations of sodium hydroxide (NaOH) solution and then grafting tertiary amine and ion‐exchange reacting with sulfonate anions. The morphology, composition, thermal stability and rheological behavior of the g ‐HNT hybrids were systematically characterized and analyzed using various methods. It is found that the viscoelasticity of g ‐HNT hybrids can be easily regulated by using different NaOH solution‐treated HNTs as inorganic core and temperatures. In addition, the g ‐HNT hybrids treated with medium concentration of NaOH (0.06 mol L −1 ) have the lowest viscosity and highest level of dispersion compared with those treated with other concentrations of NaOH solution. Due to the amphiphilic nature of g ‐HNT hybrids and their lower viscosity than HNT powder, as novel hybrid fillers, they were utilized to prepare polystyrene composites by direct melt blending for achieving simultaneous reinforcement and plasticization effects. Besides the above mentioned advantages, the thermal conductivity of polystyrene composites is also surprisingly improved by reducing the interfacial mismatch between the filler and polymer matrix. The solvent‐free and self‐reinforcement hybrids provide a convenient and green path for fabricating high‐performance polymer composites. © 2017 Society of Chemical Industry Abstract : The viscoelasticity of self‐reinforcement gel‐like halloysite nanotube ( g ‐HNT) hybrids fabricated via ion‐exchange reaction is such that they can be used as a novel plasticizer for improving the mechanical properties of polystyrene composites.